Health Care Utilisation and Attitudes towards Health Care in Subjects Reporting Environmental Annoyance from Electricity and Chemicals. (15th March 2009) - Eek, Frida; Merlo, Juan; Gerdtham, Ulf; Lithman, Thor
Abstract : Environmentally intolerant persons report decreased self-rated health and daily functioning. However, it remains unclear whether this condition also results in increased health care costs. The aim of this study was to describe the health care consumption and attitudes towards health care in subjects presenting subjective environmental annoyance in relation to the general population, as well as to a group with a well-known disorder as treated hypertension (HT). Methods . Postal questionnaire ( n = 13 604) and record linkage with population-based register on health care costs. Results . Despite significantly lower subjective well being and health than both the general population and HT group, the environmentally annoyed subjects had lower health care costs than the hypertension group. In contrast to the hypertension group, the environmentally annoyed subjects expressed more negative attitudes toward the health care than the general population. Conclusions . Despite their impaired subjective health and functional capacity, health care utilisation costs were not much increased for the environmentally annoyed group. This may partly depend on negative attitudes towards the health care in this group.